Solid oxide fuel cell (SOFC) half cell and preparation method thereof

By reducing the sintering temperature of the SOFC anode support and adopting a step-up temperature sintering process, the problems of material roughening and high cost caused by high temperature sintering in the traditional SOFC preparation process are solved, and efficient and stable SOFC half-cell preparation is achieved.

CN119133545APending Publication Date: 2024-12-13TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411211182.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

High-temperature sintering in the preparation process of traditional solid oxide fuel cells (SOFC) leads to coarse grains, phase change, high energy consumption, expensive cost and prone to cracking of the anode functional layer.

Method used

NiO-YSZ anode support powder is prepared by mixing, ball milling and extrusion, combined with step-up temperature sintering technology, to reduce the sintering temperature of the anode support, and form an anode functional layer and electrolyte layer to sinter them together at room temperature to avoid internal stress accumulation .

Benefits of technology

It effectively reduces energy consumption and preparation costs, avoids cracking of the anode functional layer, improves the performance stability and density of the SOFC half-cell, and achieves efficient electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133545A_ABST
    Figure CN119133545A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an SOFC (solid oxide fuel cell) half cell, which comprises the following steps: mixing NiO powder and YSZ powder, mixing with a pore forming agent and absolute ethyl alcohol, ball-milling to be uniform, drying, adding a first binder, and ball-milling to be uniform to obtain anode support body powder; extruding the anode support body powder into an anode support body green body, and sintering the anode support body green body in an air atmosphere to obtain an anode support body; preparing anode slurry and electrolyte slurry; coating anode slurry on the anode support body, and drying to form an anode functional layer blank layer; coating electrolyte slurry on the surface of the anode functional layer, and drying to form an electrolyte blank layer so as to obtain an SOFC half-cell biscuit; and sintering the SOFC half-cell biscuit in a stepped heating mode, and cooling to room temperature to obtain the SOFC half-cell. According to the preparation method, the process steps are optimized, and the time cost and the electric power cost are greatly saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid oxide fuel cells, and in particular to a SOFC half-cell and a preparation method thereof. Background Art

[0002] Solid Oxide Fuel Cells (SOFC) are considered to be the most efficient fuel cell. They are not affected by the Carnot cycle, and the heat cogeneration can convert fuel into energy (including heat) with an efficiency of up to 90%. SOFC is mainly composed of a cathode (usually a porous ceramic composite oxide), an anode (usually a porous ceramic metal composite) and an electrolyte (usually a single-phase oxide). SOFC can achieve efficient and rapid conversion of fuel and electricity, and is an important low-carbon energy technology. It can significantly alleviate the problems of large energy loss and ecological damage when traditional fuels such as coal and oil are burned, and at the same time, it can store excess electricity from wind and solar energy. And as a new type of power generation technology, solid oxide fuel cells can directly promote the electrochemical reaction of fuel gas (H2, CO or CH4) and oxidizing gas (O2 or air) when working, and then directly convert chemical energy into electrical energy. Since there is no combustion and mechanical movement, it has the characteristics of high efficiency, green and pollution-free. It has broad application prospects and is one of the core technologies of the future hydrogen energy industry and power industry.

[0003] The main function of the anode of SOFC is to provide a reaction site for the electrochemical oxidation reaction of the fuel, so the anode material of SOFC must be stable in a reducing atmosphere and have sufficiently high electronic conductivity and catalytic activity for the oxidation reaction of the fuel gas. Ni-based metal ceramic anode is one of the most commonly used anode materials in SOFC because of its low cost, good catalytic effect and electronic conductivity. The NiO-YSZ metal ceramic anode, which is a composite of nickel oxide (NiO) and yttria-stabilized zirconium oxide (YSZ), is the most commonly used anode material.

[0004] The traditional sintering method needs to be carried out at a higher temperature (such as 1250°C) to combine the material particles and form a dense structure to obtain battery components. However, high temperature will cause the grain coarsening and phase change of the material, and the battery is a prefabricated electrode, electrolyte and other components sintered at high temperature and then assembled, which requires higher energy consumption and more complex preparation process, thereby increasing the preparation cost. In addition, too high temperature will also affect the performance and stability of the battery. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a SOFC half-cell, which can not only reduce energy consumption and cost, but also effectively avoid cracking in the anode functional layer due to excessive stress during high-temperature sintering.

[0006] Another object of the present invention is to provide a SOFC half-cell obtained by the above preparation method.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a SOFC half-cell comprises the following steps:

[0009] S1, preparation of anode support powder: uniformly mixing NiO powder and YSZ powder, adding a pore former to obtain a mixed powder, ball milling the mixed powder until uniform, drying, adding a first binder after drying, and continuing to ball mill until uniform to obtain an anode support powder, wherein the mass ratio of NiO powder, YSZ powder, pore former and first binder is 6:4:(0.5-2.2):(0.2-0.5);

[0010] In the above step S1, the pore-forming agent is one or a mixture of cellulose, graphite powder or polymethyl methacrylate (PMMA) powder, wherein when the pore-forming agent is a mixture of graphite powder and cellulose, the mass ratio of graphite powder to cellulose is (1.5-3): (0.5-1.5), and the first binder is polyvinyl butyral (PVB).

[0011] In the above step S1, the rotation speed of the ball mill is 200-400 rpm, the ball milling time is 2-4 hours, and the ball milling medium is anhydrous ethanol.

[0012] In the above step S1, the particle size of the NiO powder is 20-30 nm.

[0013] S2, preparation of an anode support: placing an anode support powder in a mold, extruding it, taking out the mold after pressing, demolding it to obtain an anode support green body, and sintering the anode support green body in an air atmosphere to obtain an anode support;

[0014] In the above step S2, the extrusion pressure is 30-55 kN, and the extrusion time is 180-300 s.

[0015] In the above step S2, the sintering temperature is 1000-1200°C, and the sintering holding time is 2-4h.

[0016] In the above step S2, the temperature is increased to the sintering temperature at a heating rate of 0.5-3°C / min.

[0017] S3, preparation of anode slurry and electrolyte slurry:

[0018] Anode slurry: NiO powder, YSZ powder, solvent, dispersant, second binder and plasticizer are mixed, ball-milled and vacuum-defoamed to obtain anode slurry, wherein the mass fraction of NiO powder, the mass fraction of YSZ powder, the volume fraction of solvent, the volume fraction of dispersant, the mass fraction of second binder and the volume fraction of plasticizer are (5-7): (3-5): (5-15): (0.05-0.15): (2-8): (0.2-0.5), the unit of mass fraction is g, and the unit of volume fraction is mL;

[0019] Electrolyte slurry: ceramic powder, solvent, dispersant and second binder are mixed, ball milled, plasticizer and surfactant are added, ball milled continuously, and vacuum defoamed to obtain electrolyte slurry, wherein the ratio of the mass fraction of ceramic powder, the volume fraction of solvent, the volume fraction of dispersant, the mass fraction of second binder, the volume fraction of plasticizer and the volume fraction of surfactant is (20-30): (10-30): (0.1-0.3): (4-6): (0.3-0.5): (0.1-0.3), the unit of mass fraction is g, and the unit of volume fraction is mL;

[0020] In the above step S3, the second binder is one or more of polyvinyl alcohol (PVA), polyvinyl butyral (PVB) or a mixture of α-pinene alcohol and ethyl cellulose, wherein the mass ratio of α-pinene alcohol to ethyl cellulose in the mixture of α-pinene alcohol and ethyl cellulose is (4-5): (0.25-1), the solvent is anhydrous ethanol, the dispersant is one or more of phosphate ester, polyvinyl pyrrolidone or EFKA polymer dispersant (EFKA4340), the surfactant is Triton X-100 (Triton-X), the plasticizer is di-n-butyl phthalate (DBP), and the ceramic powder is YSZ powder.

[0021] In the above step S3, the rotation speed of the ball mill is 200 to 400 r / min, and the ball milling time is 2 to 24 h.

[0022] S4, preparation of anode functional layer and electrolyte layer: coating the anode support prepared in S2 with the anode slurry prepared in S3, drying at room temperature to form an anode functional layer blank, coating the surface of the anode functional layer blank with the electrolyte slurry prepared in S3, drying to form an electrolyte layer blank, and obtaining a SOFC half-cell blank;

[0023] In the above step S4, the anode slurry prepared in S3 is coated by any one of casting, screen printing, spin coating, drop coating and ultrasonic spraying.

[0024] In the above step S4, the method of coating the electrolyte slurry prepared in S3 is any one of casting, spin coating, drop coating and ultrasonic spraying.

[0025] In the above step S4, the drying temperature is 50-75° C., and the drying time is 1-4 hours.

[0026] S5, preparation of SOFC half-cell in which the anode functional layer and the electrolyte layer are co-sintered as one: the SOFC half-cell blank is heated to 550-650°C at a heating rate of 0-5°C / min by a step heating method, and sintered and kept warm for 20-40min, then heated to 950-1050°C at a heating rate of 0.5-2°C / min, sintered and kept warm for 20-40min, then heated to 350-1450°C at a heating rate of 0.8-1.2°C / min, sintered and kept warm for 4-6h, sintered for 4-8h, cooled to 750-850°C at a cooling rate of 0.5-3°C / min, and then furnace cooled to room temperature to obtain a SOFC half-cell in which the anode functional layer and the electrolyte layer are co-sintered as one.

[0027] A SOFC half-cell as described above.

[0028] In the above technical solution, the SOFC half-cell is a layered structure, including: an anode support at the bottom layer, and an anode functional layer and a dense electrolyte layer sequentially arranged on the anode support.

[0029] In the above technical solution, the thickness of the anode support of the SOFC half-cell is 500-1000 μm, the thickness of the anode functional layer of the SOFC half-cell is 20-50 μm, and the thickness of the electrolyte layer of the SOFC half-cell is 2-20 μm.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. In the preparation method of the present invention, the sintering temperature of the anode support is 1000°C, which reduces the shrinkage rate so that it can shrink more during the subsequent sintering of the electrolyte layer blank, driving the electrolyte layer blank to become dense. Compared with the traditional sintering method, the sintering process of the anode support reduces the sintering temperature and saves energy.

[0032] 2. The present invention successfully solves the problem of battery deformation and cracking caused by the accumulation of internal stress during the sintering process through a step sintering process, thereby ensuring the stable performance of the half-cell.

[0033] 3. In the preparation method of the present invention, the anode functional layer and the electrolyte layer are co-sintered integrally, which simplifies the process steps and reduces labor costs and electricity costs.

[0034] 4. The maximum power density of the SOFC half-cell prepared by the present invention with the anode functional layer and the electrolyte layer co-sintered integrally is 0.14 W cm at 700 °C. -2 The open circuit voltage (OCV) value obtained at 700°C is 1.02V, indicating that the process preparation method is feasible. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the SOFC half-cell structure prepared in Example 1;

[0036] Figure 2 This is a graph showing the shrinkage of the SOFC half-cell prepared in Example 1;

[0037] Figure 3 The open circuit voltage curve of the SOFC half-cell prepared in Example 1;

[0038] Figure 4 The IV curve and power density curve of the SOFC half-cell prepared in Example 1. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0040] In the following examples, the anode support is prepared by dry pressing, which is a preparation method in which an external force is applied to a mold to form the powder in the mold into a desired shape. When using the dry pressing method, the raw material is first processed to have an optimal packing density and particle size distribution, and then a suitable binder and dispersant are selected according to the various properties of the raw material powder. At the same time, a suitable demoulding pressure is selected according to the properties of the mold material. When the dry pressing method is used for ceramic molding, the pressure is generally not greater than 300 MPa. The ceramic blank after molding usually has good mechanical strength.

[0041] Example 1

[0042] A method for preparing a SOFC half-cell comprises the following steps:

[0043] S1, preparation of anode support powder: NiO powder and YSZ powder are mixed evenly, a pore former is added (the pore former is a mixture of graphite powder and cellulose, and the mass ratio of graphite powder to cellulose is 2:1) to obtain a mixed powder, the mixed powder is placed in a planetary ball mill, anhydrous ethanol is added as a ball milling medium, the mass ratio of anhydrous ethanol to the mixed powder is 5:1, ball milling is performed at a speed of 300 rpm for 4 hours until uniform, and then dried at room temperature for 24 hours. After drying, PVB is added, and ball milling is continued at a speed of 300 rpm for 24 hours until uniform, to obtain an anode support powder, wherein the mass ratio of NiO powder, YSZ powder, pore former and PVB is 6:4:1:0.5, the particle size of YSZ powder is 50 nm, and the particle size of NiO powder is 20 nm;

[0044] S2, preparation of an anode support: 0.4 g of an anode support powder was placed in a mold with a diameter of 15 mm, and the powder in the mold was uniaxially pressed for 180 s at a pressure of 45 kN under a four-column hydraulic press. After pressing, the mold was taken out and demolded to obtain a black disc-shaped anode support blank. In an air atmosphere, the anode support blank was heated to 1000° C. at a heating rate of 3° C. / min, sintered, and kept at 1000° C. for 2 h to obtain a green disc-shaped anode support (NiO-YSZ) with a thickness of 600 μm;

[0045] S3, preparation of anode slurry and electrolyte slurry:

[0046] Preparation of anode slurry: NiO powder, YSZ powder, anhydrous ethanol, EFKA4340, a second binder (the second binder is a mixture of α-pinene alcohol and ethyl cellulose, and the mass ratio of α-pinene alcohol to ethyl cellulose is 4.75:0.25) and DBP are mixed, ball milled at a speed of 300 r / min for 12 hours, and vacuum defoamed at 0.06 MPa to obtain an anode slurry, wherein the mass fraction of NiO powder, the mass fraction of YSZ powder, the volume fraction of anhydrous ethanol, the volume fraction of EFKA4340, the mass fraction of the second binder and the volume fraction of DBP are 6:4:10:0.1:5:0.3, the unit of mass fraction is g, and the unit of volume fraction is mL;

[0047] Preparation of electrolyte slurry: YSZ powder, anhydrous ethanol, EFKA4340 and the second binder (same as above) were ball-milled at a speed of 300 r / min for 3 h, DBP and Triton-X were added, and the ball-milling was continued at a speed of 300 r / min for 24 h, and vacuum defoaming was performed at 0.06 MPa to obtain an electrolyte slurry, wherein the mass fraction of YSZ powder, the volume fraction of anhydrous ethanol, the volume fraction of EFKA4340, the mass fraction of the second binder, the volume fraction of DBP, and the volume fraction of Triton-X were 25:20:0.2:5:0.4:0.2, the unit of mass fraction is g, and the volume fraction is mL;

[0048] S4, preparation of anode functional layer and electrolyte layer: the anode support prepared in S2 is coated with the anode slurry prepared in S3 by spin coating, and dried at room temperature for 24 hours to form an anode functional layer blank; the surface of the anode functional layer blank is coated with the electrolyte slurry prepared in S3 by spin coating, and dried at 60° C. for 2 hours to form an electrolyte layer blank, thereby obtaining a SOFC half-cell blank;

[0049] S5. Preparation of a SOFC half-cell in which an anode functional layer and an electrolyte layer are co-sintered as a whole: the SOFC half-cell blank is heated to 600°C at a heating rate of 3°C / min by a step heating method, sintered and kept at 600°C for 30 min, then heated to 1000°C at a heating rate of 1°C / min, sintered and kept at 1000°C for 30 min, then heated to 1400°C at a heating rate of 0.5°C / min, sintered and kept at 1400°C for 4 h, cooled to 800°C at a cooling rate of 3°C / min, kept at 800°C for 30 min, and then furnace cooled to room temperature to obtain a SOFC half-cell, wherein the thickness of the anode functional layer of the SOFC half-cell is 50 μm, and the thickness of the electrolyte layer of the SOFC half-cell is 20 μm.

[0050] Comparative Example 1

[0051] A method for preparing a flat anode-supported SOFC half-cell is basically the same as that in Example 1, except that in step S2, the sintering temperature of the anode support body is 1250°C, and in step S4, the anode functional layer blank layer and the electrolyte blank layer need to be sintered step by step. After the anode functional layer blank layer is dried, it is necessary to heat it to 1250°C at a heating rate of 3°C / min and sinter it at 1250°C for 2h, and then spin-coat the electrolyte slurry prepared in S3, dry it, and sinter it using the step-by-step heating method of S5 to obtain a flat anode-supported SOFC half-cell.

[0052] Figure 1This is a schematic diagram of the structure of the SOFC half-cell prepared in Example 1. In the method for preparing the SOFC half-cell in Example 1, in step S2, the temperature of sintering the anode support body is 1000°C. Compared with Comparative Example 1, the sintering temperature is lowered, and the anode support body is pressed and sintered by dry pressing to have a certain mechanical strength, saving time and electricity costs. In step S5, the anode functional layer and the electrolyte layer are co-sintered as a whole, without the need for step-by-step sintering, saving a long sintering time and saving a lot of electricity costs.

[0053] Figure 2 The shrinkage diagram of the SOFC half-cell prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the shrinkage rate decreases as the sintering temperature of the anode support decreases. Compared with Comparative Example 1, the SOFC half-cell prepared in Example 1 uses a lower sintering temperature when preparing the anode support, thereby reducing the shrinkage rate.

[0054] The SOFC half-cell prepared in Example 1 was coated with silver paste to form a full cell, and an electrochemical test was performed at a service temperature of 700°C. Figure 3 is the open circuit voltage curve of the SOFC half-cell prepared in Example 1, Figure 3 It can be seen that the open circuit voltage (OCV) value obtained at 700°C is 1.02V. Figure 4 The IV curve and power density curve of the SOFC half-cell prepared in Example 1 are shown in FIG. 1 . The power density curve is obtained according to the IV curve. Figure 4 It can be seen that the maximum power density at 700°C is 0.14 W cm -2 . Combined Figure 3 and Figure 4 , indicating that the full-cell electrolyte layer formed by coating the silver paste on the SOFC half-cell prepared in Example 1 is dense, and the preparation process is feasible.

[0055] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a SOFC half-cell, comprising the following steps: S1, preparation of anode support powder: uniformly mixing NiO powder and YSZ powder, adding a pore former to obtain a mixed powder, ball milling the mixed powder until uniform, drying, adding a first binder after drying, and continuing to ball mill until uniform to obtain an anode support powder, wherein the mass ratio of NiO powder, YSZ powder, pore former and first binder is 6:4:(0.5-2.2):(0.2-0.5); S2, preparation of an anode support: placing the anode support powder in a mold for extrusion, removing the mold after pressing, and obtaining an anode support green body after demoulding, and sintering the anode support green body in an air atmosphere to obtain an anode support; S3, preparation of anode slurry and electrolyte slurry, comprising: Preparation of anode slurry: NiO powder, YSZ powder, solvent, dispersant, second binder and plasticizer are mixed, ball milled and vacuum defoamed to obtain anode slurry, wherein the mass fraction of NiO powder, the mass fraction of YSZ powder, the volume fraction of solvent, the volume fraction of dispersant, the mass fraction of second binder and the volume fraction of plasticizer are (5-7): (3-5): (5-15): (0.05-0.15): (2-8): (0.2-0.5), the unit of mass fraction is g, and the unit of volume fraction is mL; Preparation of electrolyte slurry: ceramic powder, solvent, dispersant and second binder are mixed, ball milled, plasticizer and surfactant are added, ball milled continuously, and vacuum defoamed to obtain electrolyte slurry, wherein the ratio of the mass fraction of ceramic powder, the volume fraction of solvent, the volume fraction of dispersant, the mass fraction of second binder, the volume fraction of plasticizer and the volume fraction of surfactant is (20-30): (10-30): (0.1-0.3): (4-6): (0.3-0.5): (0.1-0.3), the unit of mass fraction is g, and the unit of volume fraction is mL; S4, preparation of anode functional layer and electrolyte layer: coating the anode support prepared in S2 with the anode slurry prepared in S3, drying at room temperature to form an anode functional layer blank, coating the surface of the anode functional layer blank with the electrolyte slurry prepared in S3, drying to form an electrolyte layer blank, and obtaining a SOFC half-cell blank; S5, preparation of SOFC half-cell in which the anode functional layer and the electrolyte layer are co-sintered as one: the SOFC half-cell blank is heated to 550-650°C by a step heating method at a heating rate of 0-5°C / min, sintered and kept warm for 20-40min, then heated to 950-1050°C at a heating rate of 0.5-2°C / min, sintered and kept warm for 20-40min, then heated to 1350-1450°C at a heating rate of 0.8-1.2°C / min, sintered and kept warm for 4-6h, cooled to 750-850°C at a cooling rate of 0.5-3°C / min, and then furnace cooled to room temperature to obtain a SOFC half-cell.

2. The preparation method according to claim 1, characterized in that: In S1, the pore-forming agent is one or a mixture of cellulose, graphite powder or polymethyl methacrylate powder, wherein when the pore-forming agent is a mixture of graphite powder and cellulose, the mass ratio of graphite powder to cellulose is (1.5-3): (0.5-1.5), and the first binder is polyvinyl butyral.

3. The preparation method according to claim 1, characterized in that: In S1, the rotation speed of the ball mill is 200-400 rpm, the ball milling time is 2-4 hours, and the ball milling medium is anhydrous ethanol.

4. The preparation method according to claim 1, characterized in that: In S2, the sintering temperature is 1000-1200°C, and the sintering holding time is 2-4h.

5. The preparation method according to claim 1, characterized in that: In S3, the rotation speed of the ball mill is 200-400 r / min, and the ball milling time is 2-24 h.

6. The preparation method according to claim 1, characterized in that: In S3, the second binder is a mixture of one or more of polyvinyl alcohol, polyvinyl butyral or a mixture of α-pinene alcohol and ethyl cellulose, wherein the mass ratio of α-pinene alcohol to ethyl cellulose in the mixture of α-pinene alcohol and ethyl cellulose is (4-5): (0.25-1), the solvent is anhydrous ethanol, the dispersant is a mixture of one or more of phosphate ester, polyvinyl pyrrolidone or Efka polymer dispersant, the surfactant is Triton X-100, the plasticizer is di-n-butyl phthalate, and the ceramic powder is YSZ powder.

7. The preparation method according to claim 1, characterized in that: In S4, the anode slurry prepared in S3 is coated by any one of casting, screen printing, spin coating, drip coating and ultrasonic spraying, and the electrolyte slurry prepared in S3 is coated by any one of casting, spin coating, drip coating and ultrasonic spraying.

8. The preparation method according to claim 1, characterized in that: In S4, the drying temperature is 50-75° C., and the drying time is 1-4 hours.

9. A SOFC half-cell, characterized in that: The SOFC half-cell is a layered structure, comprising: an anode support body at the bottom, and an anode functional layer and a dense electrolyte layer sequentially arranged on the anode support body.

10. The SOFC half-cell according to claim 9, characterized in that: The thickness of the anode support of the SOFC half-cell is 500-1000 μm, the thickness of the anode functional layer of the SOFC half-cell is 20-50 μm, and the thickness of the electrolyte layer of the SOFC half-cell is 2-20 μm.

Citation Information

Cited By

  • Preparation method and application of SOFC anode support body

    CN120600842A